The Determinants of Policing Unfounding and Prosecutorial Case Rejections in San Diego, California Sexual Assault Cases - Keller, Elizabeth M. (2003)
The vast amount of research that has been done on sexual assault in the past thirty years has yielded a great amount of knowledge bout the phenomenon of sexual assault and the way the criminal justice system responds to it. One hypothesis that emerges from this literature is that certain cases of sexual assault may be treated differently by police and.prosecutors because of characteristics of the victim, the suspect, or of the case itself This study tests that hypothesis, using data·collected by the San Diego Police Department's Sex Crimes Unit over a multi-year period in the 1990s. This study. specifically focuses on the determinants of police decisions to unfound a case (or to declare that no crime occurred) and prosecutorial decisions to decline to file charges in a case. The current study builds on past research by identifying variables (i.e. the offense severity.or the relationship between the suspect and victim) that have been previously cited as important elements in sexual assault case processing. Regression analyses will be conducted, testing both police and prosecutorial decision-making. Further regression analyses will then be conducted on sexual assault and attempted sexual assault cases specifically, allowing for comparison between these more serious cases and the others that are handled by the San Diego Police Department's Sex Crimes Unit (i.e. unlawful intercourse). The results of these analyses will be presented and comparisons between police and prosecutorial decision-making processes will be made. These results will be discussed in several different ways. First, they will be considered in relation to the specific department from which they originated and policy implications for that department will be suggested. Next, more general policy implications will be discussed, including those suggested by the variables that were not predictors of police and prosecutorial decision-making in this study. Finally, suggestions for future research will be made